Sexual dysfunction and distress in premenopausal women with migraine: association with depression, anxiety and migraine-related disability. Issue 5 (October 2018) - Kucukdurmaz, Faruk; Inanc, Yılmaz; Inanc, Yusuf; Resim, Sefa
Abstract Migraine is a chronic disorder associated with impaired quality of life as well as sexual function. However, data about the sexual distress in women with migraine were lacked.This study aimed to determine the incidence and associated risk factors of both sexual function and distress in premenopausal women with migraine. Sixty-nine women diagnosed with migraine were included. Sexual function and distress were assessed by Female sexual function index (FSFI) and Female sexual distress scale-revised (FSDS-R), respectively. Depression and anxiety were investigated by Hospital depression and anxiety scale (HADS). Migraine related disability was evaluated by Migraine disability assessment scale (MIDAS) and average severity of pain was determied by Visual analog scale (VAS). Fifty-five women reported to have sexual dysfunction. Any headache-related feature including MIDAS and VAS scores, depression or anxiety was found to be related with sexual dysfunction. Sexual distress was noted in 37 cases, and depression, VAS and MIDAS scores were significantly higher in women with sexual distress. This study showed that women with migraine should be screened both for sexual dysfunction and distress to help clinicians dealing with sexual medicine to improve the standart of patient care in their regular practice. Special attention should be given to the ones whose MIDAS and VAS scores were high and who had depression.